The model of information and communication technologybased learning for medical staff of Universitas Airlangga Hospital - Hidayat, Niko Azhari; Irianto, Jusuf; Suminar, Dewi Retno (Technium Social Sciences Journal, 2023)
The rapid development of technology started to be used in the health sector to develop the quality of human resources. Human resources need to be standardized, such as management and technology. If a hospital unit has standardized human resources in management and technology, this is an indispensable component to face competition and create a hospital with quality services. Some of the problems that are often faced by HRD at Universitas Airlangga Hospital such as selecting the right employees. This study aims to identify and analyze the model of information and communication technology-based learning for medical staff of Universitas Airlangga Hospital. This research was used a quantitative research method using primary data in the form of a questionnaire. In this study, a total of 268 respondents (n=268) gave their opinions regarding statements ranging from strongly agree, agree, normal, disagree, and strongly disagree. Then the data were analyzed by SPSS to be tested for validity, reliability, descriptive, and regression test on each variable relationship. The results of this study conclude that there are positive correlation effect between variables ranging from perceived usefullness on social influence, perceived ease of use on social influence, behavior intention on social influence, perceived usefullness on human resource development for medical staff, perceived ease of use on human resource development for medical staff, behavior intention on development of human resources for medical staff, and social influence on human resources development for medical staff.